Infiltrômetros de dimensões e formas variadas na determinação da velocidade de infiltração da água no solo sob diferentes usos - Santos, Igor Leonardo Nascimento (2018)
The infiltration of water into the soil is the main component of the hydrological cycle contributing to the storage of water in a river basin, in addition to being extremely important in agricultural areas. The test for determination of the infiltration using double-cylinder infiltrometers usually requires a large amount of water and has long durations. The purpose of this work was to use infiltrometers of reduced dimensions and varied forms in the determination of the velocity of infiltration of water in the soil under different uses. The work was conducted in the experimental area of the Rural Campus of the Federal University of Sergipe. The tests were carried out in areas managed with no-tillage, minimum tillage and conventional cultivation, cultivated with maize, where previous crops of cowpea, crotalaria, pigeon pea and millet were used. It was also carried out test in area of native forest. Four infiltrometers were used: a double cylinder infiltrometer with internal diameter of 25 cm and external diameter of 50 cm, a reduced double cylinder with internal diameter of 15 cm and external diameter of 30 cm, a single cylinder 30 cm in diameter and a double square infiltrometer with inner and outer widths of 15 and 30 cm, respectively. The double cylinder infiltrometer was considered as standard and the others (double cylinder reduced, single cylinder and double square) as alternatives. In order to compare and analyze the results of the basic infiltration velocities of the water in the soil obtained between the alternative infiltrometers and the considered standard, the criteria involving the standard error of estimation (SEE), standard error of the adjusted estimate (SEEa), standard error of the adjusted by the origin (SEEao) and determination coefficients (R2 ) were used. The influence of soil management on water infiltration capacity and performance analysis of the Horton, Kostiakov, Kostiakov-Lewis and Philip models were also analyzed using the statistical coefficients of residual mass (CRM), coefficient of adjustment (CA), and efficiency (EF). The simple infiltrometer cylinder used on average less water in the tests and obtained an equation of correction of the infiltration velocity of the water in the soil with results very close to the infiltrometer considered standard. Statistically the best results were found when using the double cylinder infiltrometer reduced. Less mechanized management benefited the process of infiltration of water into the soil. The best statistical results were obtained by the Philip model. The Horton model was able to estimate better the VIB and the Kostiakov-Lewis model did not fit well to the ground and obtained inferior results to the other methods.